How do you solve using gaussian elimination or gauss-jordan elimination, 4x-3y+z=9, 3x+2y-2z=4, x-y+3z=5?

1 Answer
Feb 11, 2018

The values x=2, y=0, and z=1 satisfy the equations
4x-3y+z=9---------(1)
3x+2y-2z=4--------(2)
x-y+3z=5-----------(3)

Explanation:

Gaussian elimination method:
4x-3y+z=9---------(1)
3x+2y-2z=4--------(2)
x-y+3z=5-----------(3)

Eliminate x from (2)
Equation (2) becomes
(2)-3/4(1)
3-3/4(4)=3-3= 0
2-3/4(-3)=2+9/4=2+2.25=4.25
-2-3/4(1)=-2-3/4=-2-0.75=-2.75
4-3/4(9)=4-6.75=-2.75
Changing the coefficients
0x+4.25y-2.75z=-2.75
4.25y-2.75z=-2.75

Eliminate x from (3)
Equation (3) becomes
(3)-1/4(1)
1-1/4(4)=1-1=0
-1-1/4(-3)=-1+0.75=-0.25
3-1/4(1)=3-0.25=2.75
5-1/4(9)=5-2.25=2.75
Changing the coefficients
0x-0.25y+2.75z=2.75
-0.25y+2.75z=2.75
Thus the equations where x is eliminated are:
4.25y-2.75z=-2.75--------(4)
-0.25y+2.75z=2.75--------(5)

Eliminate y from (5)
(3)-(-0.25)/4.25(4)
-0.25-(-0.25)/4.25(4.25)=-0.25+0.25=0
2.75-(-0.25)/4.25(-2.75)=2.75+0.162=2.912
2.75-(-0.25)/4.25(-2.75)=2.75+0.162=2.912
Changing the coefficients
0y+2.912z=2.912
2.912z=2.912
Thus, the equation where y is eliminated is
2.912z=2.912-----------(6)
Solving for z,
z=2.912/2.912=1

z=1

Substituting the value z=1 in (4)
4.25y-2.75(1)=-2.7 Simplifying5
4.25y-2.75=-2.75
Transposing -2,75 from lhs to rhs
4.25y=-2.75+2.75
4.25y=0
Solving for y
y=0/4.25

y=0

Substituting the values y=0, and z=1 in (1)
4x-3(0)y+(1)=9
Simplifying
4x-0+1=9
4x=9-1
4x=8
Solving for x

x=8/4

x=2

Check:
4(2)-3(0)+(1)=9---------(1)
3(2)+2(0)-2(1)=4--------(2)
(2)-(0)+3(1)=5-----------(3)
8-0+1=9, lhs=rhs
6+0-2=4, lhs=rhs
2-0+3=5, lhs=rhs

Thus, the values x=2, y=0, and z=1 satisfy the equations
4x-3y+z=9---------(1)
3x+2y-2z=4--------(2)
x-y+3z=5-----------(3)